Overweight and obesity trends and associated factors among reproductive women in Ethiopia - Ermias Tadesse Beyene; Seungman Cha; Yan Jin (Taylor & Francis Group, 2024)
Background In low- and middle-income countries, the double burden of malnutrition is prevalent. Many countries in Africa are currently confronted with overweight and obesity, particularly among women, coupled with an increase in the prevalence of non-communicable diseases. Objective This study examines trends in overweight and obesity among Ethiopian women of reproductive age from 2005 to 2016, and identifies associated factors. Methods We used three consecutive datasets from 2005 (n = 14070), 2011 (n = 16515), and 2016 (n = 15683) demographic health survey years. Multilevel logistic regression was used to identify the determinant factors among individual- and cluster-level variables. Results The prevalence of overweight and obesity among reproductive women in Ethiopia increased steadily from 6.09% in 2005 to 8.54% in 2011, and 10.16% in 2016. However, mixed patterns were observed among the regions of the country. We found that age, education, living in urban areas, and living in a rich community are associated with becoming overweight and obese. For instance, the odds of becoming overweight and obese among women aged 35-49 were higher than those among women aged 15-24 (odds ratio [OR] = 3.62, 95% Confidence Interval [CI]:2.64-4.97). Women who completed secondary school have higher odds than those without formal education (OR = 1.64, 95% CI:1.19-2.26). Conclusion To our knowledge, this is the first study to investigate trends in the nationwide prevalence of overweight and obesity and the associated factors among Ethiopian women. This study warrants further follow-up research to identify the pathways between overweight and obesity and their probable factors.